Performance investigation of regenerative evaporative cooled air-to-air heat recovery ventilator under different humidity conditions. (2021) - Arun, B.S.; Mariappan, V.; Anish, R.; Nimisha, P.
Abstract: To enhance the energy efficiency of an air-conditioning system air-to-air plate heat recovery ventilator can be installed to utilise the exhaust air for sensibly cooling of the ambient air. This pre-cooled intake air under low moisture content can be further cooled with a regenerative evaporative cooler. Therefore, an experimental investigation was conducted by fabricating a combined air-to-air heat exchanger and regenerative evaporative cooler test rig. The performances under low and high humidity were evaluated. Under low humidity, air-to-air heat exchanger works as sensible heat recovery ventilator, and under high humidity, it works as a dehumidifier for the regenerative evaporative cooler. The dynamic performance during the transition in humidity conditions and steady performance were studied. The results showed that the temperature below the wet-bulb temperature of intake air is achieved under low humidity. Under high humidity, condensation takes places for the intake air, increasing the latent cooling and decreasing the sensible cooling. Minimum temperature and humidity ratio of 19.9 °C and 17.05 g/kg were obtained respectively.